Getting a grip on microhabitat use and ecological performance in the chameleon Furcifer oustaleti - Clark, Ryan M. (2019)
Aim: Identifying associations between phenotype and habitat use can elucidate how species have adapted to different local environments. Organism performance capacities are key functional links between morphology and habitat use. Yet, the idea that performance is optimised in specific environmental conditions remains an untested assumption for most habitats. This paucity of data connecting environment to individuals and their functional capacities hinders attempts to build fuller understanding of adaptive systems. With this in mind, I examined chameleon optimal grip performance and tested for relationships with microhabitat use and availability.